Transcatheter aortic valve replacement: the new standard in patients with previous coronary bypass grafting? - Reinöhl, Jochen; Frankenstein, Lutz (JACC Cardiovascular interventions, 2016)
Objectives - The aim of this study was to assess how the introduction of transcatheter aortic valve replacement (TAVR) has changed clinical practice and outcome in patients who have previously undergone coronary artery bypass grafting (CABG). - Background - A significant proportion of patients admitted for aortic valve replacement have previously undergone CABG and are therefore at increased operative risk in case of redo surgery. - Methods - In-hospital outcome data were analyzed from patients with or without previous CABG undergoing isolated surgical aortic valve replacement or TAVR in Germany from 2007 to 2013. - Results - In total, 32,581 TAVR and 55,992 surgical aortic valve replacement procedures were performed in patients with (n = 6,221) or without (n = 82,352) previous CABG. TAVR increased markedly in patients with previous CABG, from 18 procedures in 2007 to 1,191 in 2013, while surgical aortic valve replacement decreased in these patients from 471 to 179 procedures. In 2013, TAVR was the preferred therapy in almost 90% of patients with previous CABG. In-hospital mortality was increased in patients with previous CABG compared with those without (7.6% vs. 6.3% for TAVR and 7.2% vs. 2.6% for surgical aortic valve replacement). Bleeding and stroke rates were also increased with redo surgical aortic valve replacement procedures (with vs. without previous CABG: stroke, 3.2% vs. 1.8%; relevant bleeding, 29.6% vs. 13.4%; acute kidney injury, 4.2% vs. 2.9%), whereas this was not the case with TAVR (stroke, 2.1% vs. 2.6%; relevant bleeding, 7.3% vs. 8.3%; acute kidney injury, 6.3% vs. 5.4% respectively). A similar influence was seen in resource utilization (discharge destination home: TAVR after CABG, 51%; surgical aortic valve replacement after CABG, 31%). - Conclusions - Since its introduction in 2007, TAVR has been increasingly used in Germany in patients with previous CABG, and in-hospital outcome data support the trend away from redo surgery.
Gesehen am 26.01.2021